Telaah Filosofis, Yuridis, dan Sosiologis dalam Konteks Hukum Islam Kontemporer terhadap Syariah dan Qanun - Annisaa, Winona Nur; Aunillah, Fahmi (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2025)
Islamic law plays a central role as the foundation in shaping the social life of Muslim communities. As time progresses and social dynamics evolve, the understanding of Islamic law has also undergone significant development. The term "Islamic law" is no longer confined to its classical interpretation but has expanded into two major concepts frequently discussed in Islamic legal literature: Sharia and Fiqh. This evolution has sparked debates and critical questions, particularly whether Islamic law is essentially the core of Sharia itself. In this study, Sharia and Qanun are viewed as closely related concepts, both rooted in the principles of Islamic law. Qanun can be understood as the practical manifestation of Sharia, formulated into regulations aimed at ensuring public welfare and societal well-being. Sharia is a set of divine norms that govern the vertical relationship between humans and Allah SWT, as well as the horizontal relationships among humans in social life. Meanwhile, Qanun refers to the legal provisions enacted by state authorities to regulate and direct public behavior toward a just and orderly society. In this context, Sharia and Qanun are not contradictory entities, but rather complementary components of a comprehensive Islamic legal system. This study employs a normative juridical method, which relies on literature review and analysis of Islamic legal sources, both primary and secondary. The normative approach aims to examine the theoretical concepts of Islamic law, Sharia, and Qanun, and to explore the interrelation between Sharia-based norms and the formulation of positive law within Muslim societies. The results of the study indicate that Islamic law constitutes the core of Sharia, while Qanun serves as the applied form of Sharia values within the context of positive law. Both elements work together to establish a legal system that is not only in harmony with religious values but also relevant to social and national life.